130k views
0 votes
I’m not sure what the answer is to this or how to do it.

I’m not sure what the answer is to this or how to do it.-example-1
User Anake
by
5.0k points

1 Answer

3 votes

Given


\begin{gathered} g(t)=t+5 \\ h(t)=3t-2 \end{gathered}

To find


(g\circ h)(-4+t)

Now,


(g\circ h)(-4+t)=g(h(-4+t))
\begin{gathered} h(-4+t)=3(-4+t)-2 \\ =3t-12-2 \\ =3t-14 \end{gathered}

Therefore,


\begin{gathered} g(h(-4+t))=g(3t-14) \\ =3t-14+5 \\ =3t-9 \end{gathered}

Hence, the correct option is (C)

User Dampee
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.